Design, synthesis and characterization of a new series of 2,3-dihydroquinazolin-4(1H)-one (DHQZ-1) derivatives and evaluation of antitumor resistant (by Molecule Docking) - Mohammed Abed Kadhim; Emad Khelil Mohammed Zangana; Arkan Hassan Jawad (مجلة بغداد للعلوم)
The objective of this work is to use multicomponent reactions (MCRs) to produce a novel series of quinazoline derivatives with high yield. This occurs in one-pot condensation among Pyridine-3-carbaldehyde with 1H-3,1-benzoxazine-2,4-dione (Isatoic anhydride) and primary amines (3-7). The mixture refluxed into tetrahydrofuran (THF, aprotic solvent). It is carried out with sodium hydrogen sulfate (NaHSO4) that is catalytically present, to afford a high yield of the 2,3-dihydroquinazolin-4(1H)-one derivative. The best yield has been obtained at 68°C. In general, all the products in the series (8-12) show a great ability as potent anticancer of the breast using a molecular docking study of the derivatives, point towards compound 11, it shows the greatest investigated as an anticancer of the breast activity than the other prepared compounds. The evaluation of molecular docking studies of derivatives is carried out via using Auto Dock 4.2 drug design software (PDB, protein code 1M17).